The Traditional Life Style and Cultural Practices of Tribal People in Tamil Nadu: An Assessment - Sudha, A (Sakha: Multidisciplinary Journal of Science, Art & Technology, 2026)
India is a diverse tapes try of numerous tribal communities. At present, indigenous tribal groups continue to inhabit the remote and forested regions of the country. With its ancient civilization, India sustains a significant population of indigenous peoples who stand as living representatives of the nation’s historical and cultural heritage. Spread across different regions, these tribal communities often live far from urban centers and continue to follow their traditional ways of life. Their livelihoods are primarily based on agriculture, hunting, and the collection of forest resources. Tribal populations maintain a close and traditional association with their territories, commonly referred to as tribal domains, where communities exercise collective rights over natural resources. Tribal human rights offer important insights into the causes, nature, and consequences of human rights violations faced by these communities. The tribal economy is largely subsistence-based or primitive in nature, with many tribes depending on cultivation, food gathering, and fruit collection for survival. Despite their rich cultural heritage, tribal communities remain among the most socially and economically marginalised groups in India.